What Characteristics Predispose to Continence in Nursing Home Residents?: A Population-Based Cross-Sectional Study - Saga, Susan (Neurourol Urodyn, 2015)
AIMS: To compare characteristics of both continent and incontinent residents in Nursing Homes (NHs) and to explore what predicts continence and severity of incontinence. METHODS: A population-based cross-sectional study was performed in nursing homes in one Norwegian municipality. Registered nurses filled in a questionnaire on behalf of the patients. RESULTS: We found that 25.4% of the NH residents were continent, 31.8% had urinary incontinence alone, 2.6% had fecal incontinence alone and 40.2% had double incontinence. Continent residents were characterized by being in short-term care, shorter stay in NH, less cognitive and physical impairment, less Parkinson's disease, stroke, constipation, and less diarrhea and more independence in activities of daily living (ADL). Residents with fecal incontinence alone were characterized by more diarrhea, less cognitive impairment and less dependency in ADL such as feeding and grooming. Residents with urinary incontinence alone were characterized by having some degree of ADL dependency, less diarrhea, and less diabetes. Residents with double incontinence were characterized by being in long-term care, a longer length of stay in NH, cognitive impairment, stroke, constipation, diarrhea, and dependency in ADL. Severity of incontinence was associated with dependency in ADL and cognitive impairment, diarrhea, length of stay in NH and lower age. CONCLUSIONS: About 25% of NH residents were continent. Double incontinence and urinary incontinence only were prevalent conditions in NHs, while FI alone was rarer. With the exception of diarrhea as a cause of FI, it appears that FI alone, UI alone, and DI may have common causes and development. Neurourol. Urodynam. 34:362–367, 2015. © 2014 The Authors. Neurourology and Urodynamics published by Wiley Periodicals, Inc.